Exploring long-term building stock strategies in Switzerland in line with IPCC carbon budgets. Issue 1 (1st September 2022) - Priore, Y D; Jusselme, T; Habert, G
Abstract: Stringent limits and reduction strategies paths on greenhouse gas (GHG) emissions are being defined at different levels for long-term temperature stabilization. Given the nearly linear relationship between warming and cumulative net emissions, a carbon budget approach is required to limit global warming, as stated by the IPCC. In this setting, the built environment, as a cross-sectorial and transnational area of activity, plays a crucial role in today's carbon emissions and future reduction potentials. Previous research showed the need for effective and aligned carbon-targets to support and guide all actors in the construction sector towards these challenging global goals. In this context, previous research compared top-down derived carbon budgets for the Swiss built environment with a preliminary estimation of future cumulative emissions of the sector. Findings showed the misalignment of current best practices and the significant magnitude of effort that would be required to comply with such objectives. Nevertheless, limitations in the preliminary work emerged, such as the lack of dynamicity of the parameters included in the model restricting the representativity of its results. The current paper brings further this previous work by integrating the dynamic evolution of the energy supply, the materials' production, and the renovation rate. Results are then presented by mean of a parallel coordinate interactive graph. This interactive component allows the parametric exploration of the compliance with limited global budgets by varying the input parameters. This way the influence of macro-level strategies to decarbonize the Swiss building stock can easily be visualized with reference to the IPCC carbon budgets. Ultimately, the available interactive tool might support policy makers in decisions taken at the building stock level.